Factors Affecting the Participating Intention in Online Voter Contact: A Case Study of Long An Province - Thanh Nhan, Nguyen (VNU Journal of Science: Policy and Management Studies, 2024)
The aim of this study is to investigate the factors influencing online voter contact intention in Long An province, based on merging the TAM (Technology Acceptance Model) and TPB (Theory of Planned Behavior) frameworks. Analysis conducted using PLS-SEM with a sample size of 201 participants reveals that perceived usefulness is the most significant predictor of participants’ attitudes. The constructs of TPB, including attitude, subjective norms, and perceived behavior control, exhibit positive and statistically significant effects on the intention to participate in online voter contact. The findings of this study have several implications for agencies involved in promoting policies related to online voter contact.